2016
DOI: 10.3892/ijo.2016.3733
|View full text |Cite
|
Sign up to set email alerts
|

ABT737 reverses cisplatin resistance by regulating ER-mitochondria Ca2+ signal transduction in human ovarian cancer cells

Abstract: Bcl-2, which belongs to the Bcl-2 family, is frequently overexpressed in various types of cancer cells and contributes to drug resistance. However, the function of Bcl-2 in cisplatin resistance in human ovarian cancer cells is not fully understood. In this study, we found that the pharmacological inhibitor ABT737 or genetic knockdown of Bcl-2 increased cisplatin cytotoxicity in cisplatin-resistant ovarian cancer cells. Additionally, treatment with ABT737 or Bcl-2 siRNA increased cisplatin-induced free Ca2+ lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…Indeed, while cisplatin by itself induces mitochondrial hyperfusion in cholangiocarcinoma cells, it induces mitochondrial fragmentation and mitophagy when co-applied with ABT-737 [48]. Moreover, in cisplatin-resistant ovarian cancer cells, ABT-737 can also promote the formation of ERmitochondrial contact sites induced by cisplatin, thereby augmenting cisplatin-induced Ca 2+ rise in the mitochondria and apoptosis [38]. These observations further underpin the intimate link between the effective response to anti-cancer therapeutics and efficient ER-mitochondrial Ca 2+ transfer [43,46,49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, while cisplatin by itself induces mitochondrial hyperfusion in cholangiocarcinoma cells, it induces mitochondrial fragmentation and mitophagy when co-applied with ABT-737 [48]. Moreover, in cisplatin-resistant ovarian cancer cells, ABT-737 can also promote the formation of ERmitochondrial contact sites induced by cisplatin, thereby augmenting cisplatin-induced Ca 2+ rise in the mitochondria and apoptosis [38]. These observations further underpin the intimate link between the effective response to anti-cancer therapeutics and efficient ER-mitochondrial Ca 2+ transfer [43,46,49].…”
Section: Discussionmentioning
confidence: 99%
“…Very interestingly, ABT-737, a non-selective Bcl-2/Bcl-XL inhibitor, can sensitize cholangiocarcinoma and ovarian cancer cells to cisplatin treatment via a mechanism that involves mitochondrial remodeling and Ca 2+ signaling [38,48]. Indeed, while cisplatin by itself induces mitochondrial hyperfusion in cholangiocarcinoma cells, it induces mitochondrial fragmentation and mitophagy when co-applied with ABT-737 [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some anticancer drugs might actually impact ER–mitochondrial contact sites and thereby enhance the response to other chemotherapeutics. For instance, ABT-737, a non-selective Bcl-2/Bcl-XL inhibitor (114, 115) could reverse the cisplatin resistance in ovarian cancer cells due to increased ER–mitochondrial Ca 2+ contact sites (116). Specifically, the authors demonstrated that ABT-737 enriched cisplatin-induced GRP75 and Mfn-2 content at the ER–mitochondria interface.…”
Section: Er–mitochondrial Ca2+ Signaling Underlying Cellular Senescenmentioning
confidence: 99%
“…Specifically, the authors demonstrated that ABT-737 enriched cisplatin-induced GRP75 and Mfn-2 content at the ER–mitochondria interface. The latter event led to enhanced mitochondrial Ca 2+ overload and subsequent cell death (116). Moreover, tumor suppressors at MAMs, including p53, were reported to modulate Ca 2+ transfer and the contact sites (54).…”
Section: Er–mitochondrial Ca2+ Signaling Underlying Cellular Senescenmentioning
confidence: 99%